2022
DOI: 10.3390/life12030436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Polyphenols on Osteoarthritis—Molecular Mechanisms

Abstract: Osteoarthritis is a common crippling and degenerative disease resulting in irreversible functional changes due to damage of the cartilage and other tissues of the joint. With limited safe and effective pharmaceutical treatments, the demand and use for alternative therapeutic approaches with symptomatic relief for OA patients have increased. Clinical, pre-clinical, and in vitro studies have demonstrated that polyphenols can exert pain-relieving symptoms coupled with increased functional capacity in OA models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 112 publications
(222 reference statements)
1
17
0
Order By: Relevance
“…A. Yay and colleagues investigated the antioxidant effect of CA on renal oxidative stress in diabetic rats induced with streptozocin [ 85 ]. Cellular ROS is generally produced at a low level in cells and is vital for maintaining cellular homeostasis and function [ 86 , 87 ]. However, an imbalance in ROS levels promotes the expression of pro-inflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…A. Yay and colleagues investigated the antioxidant effect of CA on renal oxidative stress in diabetic rats induced with streptozocin [ 85 ]. Cellular ROS is generally produced at a low level in cells and is vital for maintaining cellular homeostasis and function [ 86 , 87 ]. However, an imbalance in ROS levels promotes the expression of pro-inflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…These studies corroborated early human studies that reported that MBP improved bone mineral density in healthy and adult women (Aoe et al, 2001, 2005; Itabashi, 2006; Uenishi et al, 2007; Yamamura et al, 2002; Zou et al, 2009). Other studies found that MBP has little or no benefit to the bone health (Darling et al, 2019; Wright et al, 2017), unlike polyphenols and polyphenol‐rich diets that have been reported in several clinical trials to be beneficial in mitigating OA, RA, and OP, and other bone disorders (Nascimento Nascimento Coletro et al, 2021; Sirše, 2022). Hence, more long‐term clinical studies are needed in different populations to validate the beneficial effects of MBP and related proteins in bone health.…”
Section: Osteo‐modulatory Properties Of Food Proteins and Peptidesmentioning
confidence: 99%
“…Considering the current shortcomings in the biology of PPs, several perspectives can be envisaged to improve their safety and efficacy profiles, thanks to the increasing knowledge in basic and clinical research, and technological advances [ 6 , 8 , 241 , 242 ]. Most studies focused on the safety profiles of PPs on various cell systems in different formulations and with different delivery systems are necessary to provide more evidence-based medicine for the management of OA.…”
Section: From Basic Research To Translational Applications Of Ppsmentioning
confidence: 99%
“…Further research studies are mandatory to guarantee the safety profile of the nanofabricated delivery systems, as their use in food applications remains scarce. Regarding the regulatory aspects of nanomaterials in the medical field, there are no specific rules to guarantee the safety of encapsulated products worldwide [ 241 ]. Moreover, the sterilization processes of these systems must be considered to ensure the chemical stability of PPs and their safety in humans, which is essential for the clinical use of drugs [ 244 ].…”
Section: From Basic Research To Translational Applications Of Ppsmentioning
confidence: 99%